Coordinate- and elicitor-dependent expression of stilbene synthase and phenylalanine ammonia-lyase genes in Vitis cv. Optima - Melchior, Frauke; Kindl, Helmut (Archives of biochemistry and biophysics, 1991)
The mechanisms controlling the induction of Stilbene synthase and phenylalanine ammonia-lyase (PAL), two putative key regulatory enzymes of the biosynthetic pathway to stilbene phytoalexins, have been investigated. The induction was studied in cell suspension cultures of grape (Vitis cv. Optima) by treatment with fungal cell wall. Several independent cDNA clones for PAL and stilbene synthase were isolated from a cDNA library of fungal cell wall-induced grape cells and identified by sequence analysis. The Stilbene synthase cDNA sequence of pSV21 predicted a protein of 392 amino acids and Mr 42,791, similar in size to that observed experimentally for immunodetected stilbene synthase. The cDNA sequences of pSV21 and pSV25 differed in 76 bp in the coding region. The sequences of grape stilbene synthase cDNAs exhibited significant homology to the sequence reported for the peanut stilbene synthase cDNA. Both PAL and stilbene synthase mRNA, measured by RNA blot hybridizations, were induced within 1 h of addition of fungal cell wall preparations to the cell cultures, rose to a maximum by the sixth hour, then declined slowly over the next 20 h. The activities of PAL and stilbene synthase were also induced in parallel, but reached their maximum at different times after fungal cell wall addition to the cell cultures. The induction patterns of stilbene synthase and PAL in grape and peanut are discussed.